Edukasi Keluarga dalam Mencegah Nefropati Diabetik pada Anak dengan Diabetes Melitus untuk Mengurangi Risiko Cuci Darah - Bun Yurizali; Nurmaines Adhyka (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Unhealthy snack consumption among early childhood remains a public health concern that may increase the risk of chronic diseases, including kidney disorders, later in life. Families, particularly parents, play a strategic role in shaping children’s eating habits. This community service program aimed to improve parental knowledge and commitment in selecting healthy snacks as an effort to prevent nephropathy risk in children. The activity was conducted at Citra Almadina Kindergarten, Padang City, involving 40 parents as participants. The methods included interactive education sessions, discussions, and practical workshops on reading nutrition labels and preparing healthy lunch menus. Evaluation was carried out by assessing parents’ perceptions, knowledge, and behavioral commitment. The results showed that all children had daily snacking habits dominated by snacks high in sugar, salt, and fat. After the educational intervention, parents demonstrated increased awareness of the health risks of unhealthy snacks and the importance of limiting sugar, salt, and fat intake. As many as 87.5% of participants committed to being more selective in choosing snacks for their children, 75% committed to regularly providing home-prepared meals, and 95% committed to limiting sweet and salty snacks. In conclusion, this community service activity was effective in enhancing family awareness and readiness to actively participate in preventing health risks in children through better control of snack consumption.